Discipline Strategies: Parent’s Experiences for Early Childhood Development in North Eastern, Thailand - Sangsuk, Nisachol; Thipchart, Thiranun (Jurnal Keperawatan Soedirman, 2023)
Parent’s positive discipline strategies are very important to promote child development. However, the use of corporal punishment, psychological, physical, and sexual violence to child in the Southern Thailand is quite high. This study aimed to explore phenomenon of interest in the contextual relationship between parents’ discipline strategies and early childhood development and behaviors. This study employed a qualitative hermeneutic phenomenological approach. Sampling method using a purposive sampling strategy, potential participants who met the initial criteria were the primary caregivers, closely live with the children, and regarded to have had adequate experience with child rearing. The principle of data saturation was used to recruit 8 study informants. Thematic statements were identified from narrative data. Pattern of themes were interpreted by using a qualitative hermeneutic phenomenological approach. Trustworthiness of data was established following Lincoln and Guba’s criteria. This study found 4 themes included: 1) Parents’ positive discipline strategies, 2) Ineffective methods in disciplined the child, 3) Low self-discipline children lacked of self-control and poor emotional regulation, and 4) Disciplined children were full of self-regulation. Strengthen self-control and self-regulation should be done for training children to become disciplined. Parents should be trained positive discipline techniques for improving children’s behaviors